A wear-resistant lining for ball mill
By designing a wear-resistant lining structure including boron-permeable layer and wear-resistant coating on the ball mill lining, the problem of insufficient wear-resistant performance of the existing ball mill lining is solved, and higher hardness and wear-resistant performance are achieved, extending service life and improving quality.
Patent Information
- Application Number
- CN202311700684.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-12
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-12-12
AI Technical Summary
The existing ball mill linings have relatively poor wear resistance, which affects their service life and quality.
The ball mill wear-resistant lining design is adopted, including a lining substrate, a boron-permeable layer and a wear-resistant coating. The wear-resistant coating consists of a specific weight part of raw material and is formed through a complex preparation process, including the preparation of spherical substrates, the preparation of wear-resistant additives, and the spraying and curing of coatings.
It significantly improves the hardness and wear resistance of the ball mill lining plate, extends the service life and ensures quality.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wear-resistant materials, in particular to a wear-resistant lining plate for a ball mill. Background Art
[0002] Ball mill is a commonly used grinding or grinding equipment. It is composed of a horizontal cylinder, a hollow shaft for feeding and discharging materials, and a grinding head. The cylinder is a long cylinder with grinding bodies inside. The cylinder is made of steel plate and fixed with a steel liner. The grinding bodies are generally steel balls and are loaded into the cylinder according to different diameters and a certain proportion. The grinding bodies can also be steel segments. Ball mills are mainly used in cement, silicate products, new building materials, refractory materials, fertilizers, black and non-ferrous metal beneficiation, glass and ceramics and other production industries.
[0003] The ball mill liner is used to protect the cylinder from direct impact and friction between the grinding body and the material. At the same time, different forms of liners can be used to adjust the movement state of the grinding body to enhance the grinding effect of the grinding body on the material, which helps to improve the grinding efficiency of the mill, increase production, and reduce metal consumption. In the patent document with application number "CN104152815B" and name "A ball mill liner", a ball mill liner is disclosed, including the following chemical components in weight percentage: C1.05-1.35%, Si0.30-0.90%, Mn16-19%, Cr1.50-2.50%, Ni4-6%, Re0.30-1.00%, P≤0.06%, S≤0.04%, and the balance is Fe.
[0004] Although the ball mill liner provided in the above patent document has good toughness and impact resistance, its wear resistance is relatively poor, which not only affects its service life to a certain extent, but also affects its quality. Therefore, the present invention provides a ball mill wear-resistant liner to solve the above technical problems. Summary of the invention
[0005] The object of the present invention is to provide a wear-resistant lining for a ball mill. The provided ball mill lining not only has good toughness and impact resistance, but also has excellent hardness and wear resistance, which prolongs its service life to a certain extent and also ensures its quality.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A ball mill wear-resistant lining, comprising a lining substrate, a boronized layer and a wear-resistant coating; the surface of the wear-resistant lining is provided with the boronized layer and the wear-resistant coating in sequence from the inside to the outside;
[0008] The coating used for the wear-resistant coating is composed of the following raw materials in parts by weight: 50 to 60 parts of poly(naphthalene)diphenyl ether sulfone, 30 to 50 parts of poly(naphthalene)diphenyl ether ketone, 8 to 12 parts of polytetrafluoroethylene, 5 to 8 parts of wear-resistant additives, 2 to 5 parts of tungsten disulfide, 3 to 4 parts of graphite, 2 to 3 parts of aluminum oxide, 3 to 5 parts of silicon carbide and 80 to 100 parts of N-methyl-2-pyrrolidone.
[0009] Furthermore, the preparation method of the wear-resistant additive is:
[0010] Step 1: adding the spherical substrate into a 0.05-0.08 mol / L aqueous solution of ammonium molybdate at a solid-liquid ratio of 0.005-0.01 g / L, and then adding thioacetamide in a molar amount 5-8 times that of ammonium molybdate, mixing and stirring evenly, transferring the mixture into a reaction kettle, and reacting at a temperature of 200-230° C. for 10-20 hours;
[0011] Step 2: After the reaction is completed, the resulting components are naturally cooled to room temperature, and then solid-liquid separation is performed. The obtained filter cake is washed alternately with deionized water and anhydrous ethanol for 2 to 3 times, and then transferred to a vacuum drying oven and dried at a temperature of 60 to 70° C. After drying, the obtained solid powder is put into oleic acid with a mass of 30 to 50 times that of the solid powder, ultrasonically mixed and then soaked for 30 to 50 hours;
[0012] Step 3: After soaking, remove excess oleic acid by centrifugation, and sinter the soaked solid powder at 600-1000° C. for 3-7 hours under the protection of nitrogen atmosphere; after sintering, cool it naturally to room temperature, and the final product is a wear-resistant additive.
[0013] Furthermore, the preparation method of the spherical substrate is as follows: three equal parts of boron oxide are slowly added into methanol in three batches at a molar ratio of 1:3; after sufficient reaction, the obtained solution is atomized into micron droplets by ultrasonic atomization; the micron droplets are blown into a reactor by nitrogen, and a step heating reaction is carried out under the protection of nitrogen; after the reaction is completed, the introduction of ammonia is stopped, and the temperature in the reactor is naturally reduced to below 550°C under the protection of a nitrogen atmosphere; the white solid product is collected, and then washed with methanol 2 to 3 times, and finally centrifuged and dried to obtain a spherical substrate.
[0014] Furthermore, the specific process of the step heating reaction is: raising the temperature in the reaction furnace to 1200-1300°C; turning off the nitrogen and introducing ammonia into the reaction furnace at a flow rate of 2-3L / min, continuing to raise the temperature to 1300-1400°C, and then introducing nitrogen and ammonia into the nitriding furnace at a flow rate of 1-2L / min, respectively, and keeping the temperature for reaction for 50-70min.
[0015] Furthermore, the wear-resistant lining of the ball mill is composed of the following raw materials in weight percentage: C: 0.6-1.5%; Si: 0.5-0.8%; Mn: 0.9-1.5%; Cr: 2.0-2.6%; Mo: 0.2-0.4%; Al: 0.025-0.045%; W: 0.3-0.7%; Ni: 0.6-1.0%; Re: 0.04-0.08%; P≤0.05%; S≤0.03%; the remainder is Fe and unavoidable impurities.
[0016] Furthermore, the Re is selected from any one of Nd, La, and Ce.
[0017] Furthermore, the method for preparing the boronized layer is as follows: the lining substrate is heated to 850-880°C and then heat treated for 220-260 minutes, then slowly cooled to 600°C and placed in a boronizing agent, and heat treated at 920-960°C for 5-6 hours, so that a boronized layer with a thickness of 0.2-0.3 mm is formed on the surface of the lining substrate.
[0018] Furthermore, the boronizing agent is made of the following raw materials in percentage by mass: 15-25% silicon carbide, 3-8% lanthanum oxide, and the balance is anhydrous borax; and the average particle size of silicon carbide and lanthanum oxide is ≤60 μm.
[0019] Furthermore, the preparation method of the wear-resistant coating is as follows: the raw materials in the coating used for the wear-resistant coating are mixed evenly and then sprayed on the surface of the lining substrate, and then transferred into an oven and kept warm at a temperature of 200-250°C for 3-4 hours; after the N-methyl-2-pyrrolidone is fully volatilized, it is dried; then, it is kept warm and cured at a temperature of 380-420°C for 50-70 minutes, and finally sintered, turned and ground into a film layer with a thickness of 0.03-0.05 mm, and the resulting film is the wear-resistant coating.
[0020] Furthermore, the average particle sizes of the polytetrafluoroethylene, tungsten disulfide, graphite, aluminum oxide and silicon carbide are all 3-6 μm.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] In the present invention, boron oxide and methanol are used as starting materials, and the products obtained by the reaction of the two are blown into a reaction furnace by ultrasonic atomization, and step heating reaction is carried out under the protection of nitrogen atmosphere, and finally, boron nitride nano-microspheres with spherical structure, i.e. inorganic carrier microspheres, are prepared after washing, centrifugation and drying. The obtained inorganic carrier microspheres are put into an ammonium molybdate aqueous solution, and then thioacetamide is added thereto, and a dense film layer formed by spherical molybdenum disulfide is deposited on the surface of the inorganic carrier microspheres after chemical reaction. Under the synergistic cooperation of the boron nitride nano-microspheres and the spherical molybdenum disulfide film layer densely stacked and distributed on their surfaces, the wear resistance of the inorganic carrier microspheres is significantly improved. The solid powder obtained after the reaction is put into oleic acid, and after ultrasonic mixing, soaking, and high-temperature sintering in a centrifuge, a carbon envelope layer is finally coated on the surface of the obtained solid powder, and finally a wear-resistant additive is prepared, and the presence of the carbon envelope layer further improves the wear resistance of the wear-resistant additive. The wear-resistant additive prepared by the present invention is composed of boron nitride nano-microspheres, spherical molybdenum disulfide and a carbon envelope layer, which makes the prepared wear-resistant additive have excellent hardness and wear resistance. It is used as a raw material for preparing a wear-resistant coating and can greatly improve the self-lubricating wear resistance of a ball mill liner.
[0023] In addition, the presence of the boronized layer in the present invention effectively improves the impact strength and wear resistance of the ball mill liner, and cooperates with the wear-resistant coating to further improve the wear resistance of the ball mill liner and ensure its quality. DETAILED DESCRIPTION
[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example
[0025] A wear-resistant lining plate for a ball mill, comprising a lining plate substrate, a boronized layer and a wear-resistant coating; the surface of the wear-resistant lining plate is provided with the boronized layer and the wear-resistant coating in sequence from the inside to the outside;
[0026] The paint used for the wear-resistant coating is composed of the following raw materials in parts by weight: 50 parts of poly(naphthalene)diphenyl ether sulfone, 30 parts of poly(naphthalene)diphenyl ether ketone, 8 parts of polytetrafluoroethylene, 5 parts of wear-resistant additives, 2 parts of tungsten disulfide, 3 parts of graphite, 2 parts of aluminum oxide, 3 parts of silicon carbide and 80 parts of N-methyl-2-pyrrolidone; the average particle size of polytetrafluoroethylene, tungsten disulfide, graphite, aluminum oxide and silicon carbide is 3 μm.
[0027] The preparation method of the wear-resistant additive is:
[0028] Step 1: put the spherical substrate into a 0.05 mol / L aqueous solution of ammonium molybdate at a solid-liquid ratio of 0.005 g / L, then add thioacetamide in a molar amount 5 times that of ammonium molybdate, mix and stir evenly, transfer it into a reactor, and keep it at 200° C. for 10 hours;
[0029] Step 2: After the reaction is completed, the product components are naturally cooled to room temperature, and then solid-liquid separation is performed. The obtained filter cake is washed twice with deionized water and anhydrous ethanol alternately, and then transferred to a vacuum drying oven and dried at a temperature of 60°C; after drying, the obtained solid powder is put into oleic acid with a mass of 30 times that of the solid powder, ultrasonically mixed and then soaked for 30 hours;
[0030] Step 3: After soaking, remove excess oleic acid by centrifugation, and sinter the soaked solid powder at 600° C. for 3 hours under the protection of nitrogen atmosphere; after sintering, cool it naturally to room temperature, and the final product is a wear-resistant additive.
[0031] The preparation method of the spherical substrate is as follows: three equal parts of boron oxide are slowly added into methanol in three batches at a molar ratio of 1:3; after sufficient reaction, the obtained solution is atomized into micron droplets by ultrasonic atomization; the micron droplets are blown into a reaction furnace by nitrogen, and a step heating reaction is carried out under the protection of nitrogen; after the reaction is completed, the introduction of ammonia is stopped, and the temperature in the reaction furnace is naturally reduced to below 550°C under the protection of a nitrogen atmosphere; a white solid product is collected, and then washed twice with methanol, and finally centrifuged and dried to obtain a spherical substrate.
[0032] The specific process of the step heating reaction is as follows: raising the temperature in the reaction furnace to 1200°C; turning off the nitrogen and introducing ammonia into the reaction furnace at a flow rate of 2L / min, continuing to raise the temperature to 1300°C, and then introducing nitrogen and ammonia into the nitriding furnace at a flow rate of 1L / min respectively, and keeping the temperature for reaction for 50 minutes.
[0033] The wear-resistant lining of the ball mill is composed of the following raw materials in weight percentage: C: 0.6%; Si: 0.5%; Mn: 0.9%; Cr: 2.0%; Mo: 0.2%; Al: 0.025%; W: 0.3%; Ni: 0.6%; Nd: 0.04%; P: 0.05%; S: 0.03%; the balance is Fe and unavoidable impurities.
[0034] The method for preparing the boronized layer is as follows: the lining substrate is heated to 850°C and then heat treated for 220 minutes, then slowly cooled to 600°C and placed in a boronizing agent, and heat treated at 920°C for 5 hours, so that a boronized layer with a thickness of 0.2 mm is formed on the surface of the lining substrate.
[0035] The boronizing agent is made of the following raw materials in percentage by mass: 15% silicon carbide, 3% lanthanum oxide, and the balance is anhydrous borax; and the average particle size of silicon carbide and lanthanum oxide is 60 μm.
[0036] The preparation method of the wear-resistant coating is as follows: the raw materials in the coating used for the wear-resistant coating are mixed evenly and then sprayed on the surface of the lining substrate, and then transferred into an oven and kept warm at 200°C for 3 hours; after the N-methyl-2-pyrrolidone is fully volatilized, it is dried; then it is kept warm and cured at 380°C for 50 to 70 minutes, and finally sintered, turned and ground into a film layer with a thickness of 0.03 mm, and the obtained film is the wear-resistant coating. Example
[0037] The difference between this embodiment and embodiment 1 is that the specific ratio of the wear-resistant coating, the specific composition of the wear-resistant lining of the ball mill and the preparation method of the wear-resistant additive are different. The specific ratio of the wear-resistant coating, the specific composition of the wear-resistant lining of the ball mill and the preparation method of the wear-resistant additive in this embodiment are as follows:
[0038] The paint used for the wear-resistant coating is composed of the following raw materials in parts by weight: 55 parts of poly(naphthalene)diphenyl ether sulfone, 40 parts of poly(naphthalene)diphenyl ether ketone, 10 parts of polytetrafluoroethylene, 6 parts of wear-resistant additives, 3 parts of tungsten disulfide, 3.5 parts of graphite, 2.5 parts of aluminum oxide, 4 parts of silicon carbide and 90 parts of N-methyl-2-pyrrolidone; the average particle size of polytetrafluoroethylene, tungsten disulfide, graphite, aluminum oxide and silicon carbide is 5 μm.
[0039] The preparation method of the wear-resistant additive is:
[0040] Step 1: put the spherical substrate into a 0.06 mol / L aqueous solution of ammonium molybdate at a solid-liquid ratio of 0.008 g / L, then add thioacetamide in a molar amount 6 times that of ammonium molybdate, mix and stir evenly, transfer it into a reactor, and keep it at a temperature of 220° C. for 15 hours;
[0041] Step 2: After the reaction is completed, the resulting components are naturally cooled to room temperature, and then solid-liquid separation is performed. The obtained filter cake is washed alternately with deionized water and anhydrous ethanol for 3 times, and then transferred to a vacuum drying oven and dried at a temperature of 65°C; after drying, the obtained solid powder is put into oleic acid with a mass of 40 times that of the solid powder, ultrasonically mixed and then soaked for 40 hours;
[0042] Step 3: After soaking, remove excess oleic acid by centrifugation, and sinter the soaked solid powder at 800° C. for 5 hours under the protection of nitrogen atmosphere; after sintering, cool it naturally to room temperature, and the final product is a wear-resistant additive.
[0043] The preparation method of the spherical substrate is as follows: three equal parts of boron oxide are slowly added into methanol in three batches at a molar ratio of 1:3; after sufficient reaction, the obtained solution is atomized into micron droplets by ultrasonic atomization; the micron droplets are blown into a reaction furnace by nitrogen, and a step heating reaction is carried out under the protection of nitrogen; after the reaction is completed, the introduction of ammonia is stopped, and the temperature in the reaction furnace is naturally reduced to below 550°C under the protection of a nitrogen atmosphere; a white solid product is collected, and then washed with methanol 3 times, and finally centrifuged and dried to obtain a spherical substrate.
[0044] The wear-resistant lining of the ball mill is composed of the following raw materials in weight percentage: C: 1.0%; Si: 0.6%; Mn: 1.2%; Cr: 2.3%; Mo: 0.3%; Al: 0.035%; W: 0.5%; Ni: 0.8%; La: 0.06%; P: 0.045%; S: 0.025%; the balance is Fe and unavoidable impurities. Example
[0045] The difference between this embodiment and embodiment 1 is that the specific ratio of the wear-resistant coating, the specific composition of the wear-resistant lining of the ball mill and the preparation method of the wear-resistant additive are different. The specific ratio of the wear-resistant coating, the specific composition of the wear-resistant lining of the ball mill and the preparation method of the wear-resistant additive in this embodiment are as follows:
[0046] The paint used for the wear-resistant coating is composed of the following raw materials in parts by weight: 60 parts of poly(naphthalene)diphenyl ether sulfone, 50 parts of poly(naphthalene)diphenyl ether ketone, 12 parts of polytetrafluoroethylene, 8 parts of wear-resistant additives, 5 parts of tungsten disulfide, 4 parts of graphite, 3 parts of aluminum oxide, 5 parts of silicon carbide and 100 parts of N-methyl-2-pyrrolidone; the average particle size of polytetrafluoroethylene, tungsten disulfide, graphite, aluminum oxide and silicon carbide is 6 μm.
[0047] The preparation method of the wear-resistant additive is:
[0048] Step 1: put the spherical substrate into a 0.08 mol / L aqueous solution of ammonium molybdate at a solid-liquid ratio of 0.01 g / L, then add thioacetamide in a molar amount 8 times that of ammonium molybdate, mix and stir evenly, transfer it into a reactor, and keep it at 230° C. for 20 hours;
[0049] Step 2: After the reaction is completed, the product components are naturally cooled to room temperature, and then solid-liquid separation is performed. The obtained filter cake is washed alternately with deionized water and anhydrous ethanol for 3 times, and then transferred to a vacuum drying oven and dried at a temperature of 70°C; after drying, the obtained solid powder is put into oleic acid with a mass of 50 times that of the solid powder, ultrasonically mixed and then soaked for 50 hours;
[0050] Step 3: After soaking, remove excess oleic acid by centrifugation, and sinter the soaked solid powder at 1000° C. for 7 hours under the protection of nitrogen atmosphere; after sintering, cool it naturally to room temperature, and the final product is a wear-resistant additive.
[0051] The preparation method of the spherical substrate is as follows: three equal parts of boron oxide are slowly added into methanol in three batches at a molar ratio of 1:3; after sufficient reaction, the obtained solution is atomized into micron droplets by ultrasonic atomization; the micron droplets are blown into a reaction furnace by nitrogen, and a step heating reaction is carried out under the protection of nitrogen; after the reaction is completed, the introduction of ammonia is stopped, and the temperature in the reaction furnace is naturally reduced to below 550°C under the protection of a nitrogen atmosphere; a white solid product is collected, and then washed with methanol 3 times, and finally centrifuged and dried to obtain a spherical substrate.
[0052] The wear-resistant lining of the ball mill is composed of the following raw materials in weight percentage: C: 1.5%; Si: 0.8%; Mn: 1.5%; Cr: 2.6%; Mo: 0.4%; Al: 0.045%; W: 0.7%; Ni: 1.0%; Ce: 0.08%; P: 0.04%; S: 0.02%; the balance is Fe and unavoidable impurities.
[0053] Comparative Example 1: The difference from Example 1 is that in this example, the surface of the wear-resistant lining plate is not subjected to boronizing treatment;
[0054] Comparative Example 2: The difference from Example 1 is that the surface of the wear-resistant lining in this example does not contain a wear-resistant coating;
[0055] Comparative Example 3: The difference from Example 1 is that in this example, an equal amount of spherical substrate is used to replace the wear-resistant additive;
[0056] Performance test: The ball mill wear-resistant lining samples provided in Examples 1 to 3 and Comparative Examples 1 to 3 are respectively marked as Examples 1 to 3 and Comparative Examples 1 to 3; and the relevant properties of the ball mill wear-resistant lining provided in Examples 1 to 3 and Comparative Examples 1 to 3 are respectively tested as follows, and the obtained data are recorded in the following table:
[0057] By comparing and analyzing the relevant data in the table, it can be seen that the ball mill liner provided by the present invention not only has good toughness and impact resistance, but also has excellent hardness and wear resistance, which prolongs its service life to a certain extent and also guarantees its quality. Therefore, it shows that the ball mill wear-resistant liner provided by the present invention has a broader market prospect and is more suitable for promotion.
[0058] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0059] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A wear-resistant lining plate for a ball mill, characterized in that: The wear-resistant lining of the ball mill comprises a lining substrate, a boronized layer and a wear-resistant coating; the surface of the wear-resistant lining is provided with the boronized layer and the wear-resistant coating in sequence from the inside to the outside; The coating used for the wear-resistant coating is composed of the following raw materials in parts by weight: 50-60 parts of poly(naphthalene)diphenyl ether sulfone, 30-50 parts of poly(naphthalene)diphenyl ether ketone, 8-12 parts of polytetrafluoroethylene, 5-8 parts of wear-resistant additives, 2-5 parts of tungsten disulfide, 3-4 parts of graphite, 2-3 parts of aluminum oxide, 3-5 parts of silicon carbide and 80-100 parts of N-methyl-2-pyrrolidone; The wear-resistant additive is boron nitride nano-microspheres, on the surface of which a spherical molybdenum disulfide dense film layer is deposited and a carbon envelope layer is coated in sequence.
2. A wear-resistant lining plate for a ball mill according to claim 1, characterized in that: The preparation method of the wear-resistant additive is: Step 1: adding the spherical substrate into a 0.05-0.08 mol / L aqueous solution of ammonium molybdate at a solid-liquid ratio of 0.005-0.01 g / L, and then adding thioacetamide in a molar amount 5-8 times that of ammonium molybdate, mixing and stirring evenly, transferring the mixture into a reaction kettle, and reacting at a temperature of 200-230° C. for 10-20 hours; Step 2: After the reaction is completed, the resulting components are naturally cooled to room temperature, and then solid-liquid separation is performed. The obtained filter cake is washed alternately with deionized water and anhydrous ethanol for 2 to 3 times, and then transferred to a vacuum drying oven and dried at a temperature of 60 to 70° C. After drying, the obtained solid powder is put into oleic acid with a mass of 30 to 50 times that of the solid powder, ultrasonically mixed and then soaked for 30 to 50 hours; Step 3: After soaking, remove excess oleic acid by centrifugation, and sinter the soaked solid powder at a temperature of 600-1000° C. for 3-7 hours under the protection of nitrogen atmosphere; After sintering is completed, it is naturally cooled to room temperature, and the final product is a wear-resistant additive.
3. A ball mill wear-resistant lining according to claim 2, characterized in that: The preparation method of the spherical substrate is as follows: three equal parts of boron oxide are slowly added into methanol in three batches at a molar ratio of 1:3; after sufficient reaction, the obtained solution is atomized into micron droplets by ultrasonic atomization; the micron droplets are blown into a reaction furnace by nitrogen gas, and a step heating reaction is carried out under the protection of nitrogen gas; after the reaction is completed, the introduction of ammonia gas is stopped, and the temperature in the reaction furnace is naturally reduced to below 550° C. under the protection of nitrogen atmosphere; a white solid product is collected, and then washed with methanol for 2 to 3 times, and finally centrifuged and dried to obtain a spherical substrate.
4. A wear-resistant lining plate for a ball mill according to claim 3, characterized in that: The specific process of the step heating reaction is: raising the temperature in the reaction furnace to 1200-1300°C; turning off the nitrogen and introducing ammonia into the reaction furnace at a flow rate of 2-3L / min, continuing to raise the temperature to 1300-1400°C, and then introducing nitrogen and ammonia into the nitriding furnace at a flow rate of 1-2L / min, respectively, and keeping the temperature for reaction for 50-70min.
5. The wear-resistant lining plate for a ball mill according to claim 1, characterized in that: The wear-resistant lining of the ball mill is composed of the following raw materials in weight percentage: C: 0.6-1.5%; Si: 0.5-0.8%; Mn: 0.9-1.5%; Cr: 2.0-2.6%; Mo: 0.2-0.4%; Al: 0.025-0.045%; W: 0.3-0.7%; Ni: 0.6-1.0%; Re: 0.04-0.08%; P≤0.05%; S≤0.03%; the balance is Fe and unavoidable impurities.
6. A wear-resistant lining plate for a ball mill according to claim 5, characterized in that: The Re can be selected from any one of Nd, La, and Ce.
7. The wear-resistant lining plate for a ball mill according to claim 1, characterized in that: The method for preparing the boronized layer is as follows: heating the lining substrate to 850-880°C and then heat treating it for 220-260 minutes, then slowly cooling it to 600°C and placing it in a boronizing agent, and heat treating it at 920-960°C for 5-6 hours, so that a boronized layer with a thickness of 0.2-0.3 mm is formed on the surface of the lining substrate.
8. The wear-resistant lining plate for a ball mill according to claim 7, characterized in that: The boronizing agent is made of the following raw materials in percentage by mass: 15-25% of silicon carbide, 3-8% of lanthanum oxide, and the balance is anhydrous borax; and the average particle size of silicon carbide and lanthanum oxide is ≤60 μm.
9. The wear-resistant lining plate for a ball mill according to claim 1, characterized in that: The preparation method of the wear-resistant coating is as follows: the raw materials in the coating used for the wear-resistant coating are mixed evenly and then sprayed on the surface of the lining substrate, and then transferred into an oven and heat-treated at a temperature of 200-250° C. for 3-4 hours; after the N-methyl-2-pyrrolidone is fully volatilized, it is dried; then, it is heat-cured at a temperature of 380-420° C. for 50-70 minutes, and finally sintered, turned and ground into a film layer with a thickness of 0.03-0.05 mm, and the obtained film layer is the wear-resistant coating.
10. The wear-resistant lining plate for a ball mill according to claim 1, characterized in that: The average particle sizes of the polytetrafluoroethylene, tungsten disulfide, graphite, aluminum oxide and silicon carbide are all 3-6 μm.
Citation Information
Patent Citations
A ball mill liner
CN104152815B
VN (Vanadium Nitride) wear-resisting coating with low abrasion rate and preparation method thereof
CN103726014A
Preparation method of high-purity phase spherical molybdenum disulfide
CN105776335A